Identification and Assessment of the Severity of the Infusion Related Reactions of Medications - N, Sreelalitha; E, Vigneshwaran; G, Narayana; RY, Padmanabha; R M, Ramakesava (Indian Journal of Pharmacy Practice)
Objective: To identify infusion related reactions (IRRs) of medications. To establish the causality relationship between the drug and IRRs and to assess the severity of IRRs. Methodology: The required data were collected from the various sources such as patients' case reports, treatment charts and through direct patient interview. The obtained data was evaluated for their severity according to the Common Terminology Criteria for Adverse Events v4.0 (CTCAE).The causal relationship between the drug and the reaction was established by using the Naranjo scale and WHO causality assessment scale. Results and Discussion: A total of 75 IRRs were reported in the six months period. Most of the IRRs were developed in the patients receiving anti-cancer agents and antibiotics are next to them. According to Naranjo scale out of 75 IRRs 30% were probably have a causal relationship with the drug and remaining 70% were possibly related to drug given through infusion and according to WHO Severity assessment 3% reactions were certain, 39% were probable, 52% were possible and 6% were unlikely. Based on the Common Terminology Criteria for Adverse Events v4.0 (CTCAE) revealed that the 28% were at grade 1, 57% were at grade 2 and 13% were at grade 3 severity. Conclusion: Infusion related reactions monitoring is important as it may prevents the complications which may occur in future. Awareness of infusion-related reactions is necessary, and the risk factors associated with these reactions may have important clinical implications.
Keywords: Infusion related reactions; Causality assessment; Common Terminology Criteria for Adverse Events v4.0